Current Insights in Pollen Allergens - Jimenez-Lopez, Jose C. (IntechOpen, 2012)
The present edition of "Current Insights in Pollen Allergens" provides recent aspects related to pollen allergy, a major medical problem which is still under thorough studies. The chapters of this book will be of significant value to those interested to get notions about molecular basis of pollen allergy, such as allergen proteins polymorphism and its implications in allergic disease, cross-reactivity between pollen and pollen-plant food derived allergens, as well as strategies for clinical trial and future research. This book also provides insights about the application of molecular tools in allergens detection and quantification such as "multiplex methods", helping in the development of the standardization process of pollen protein extracts, ensuring efficiency and safety in allergy diagnosis and immunotherapy, but also exploring factors that affect allergen product expression (environmental factors), and alternative effective anti-allergic and/or preventative strategies for allergic diseases.